2017
DOI: 10.1590/s0104-12902017170669
|View full text |Cite
|
Sign up to set email alerts
|

Narrativas sobre risco e culpa entre usuários e usuárias de um serviço especializado em infecções por HIV: implicações para o cuidado em saúde sexual

Abstract: Narrativas sobre risco e culpa entre usuários e usuárias de um serviço especializado em infecções por HIV: implicações para o cuidado em saúde sexual AbstractThe objective of this study is to understand how perceptions about HIV and AIDS are articulated in narratives of male and female patients of the Public Health System, with qualitative elements that demonstrate the importance of sexual health counseling. Nine male and female patients of a specialized health service (CTA) were interviewed in Porto Alegre wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
(14 reference statements)
0
5
0
7
Order By: Relevance
“…A study, which pointed out women's narratives focused on the exposure of sexuality and the loss of trust in their partners, resumes, somehow, a discourse associated with the idea of romantic love, fidelity, respect and complicity that were historically constructed in the West (4) . In another study, carried out in the United States, Australia and Europe, it was revealed that people with high-risk heterosexual activity, due to not realizing that they are at high risk of contracting HIV, ended up contributing to the late diagnosis of HIV associated with heterosexual transmission (24) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study, which pointed out women's narratives focused on the exposure of sexuality and the loss of trust in their partners, resumes, somehow, a discourse associated with the idea of romantic love, fidelity, respect and complicity that were historically constructed in the West (4) . In another study, carried out in the United States, Australia and Europe, it was revealed that people with high-risk heterosexual activity, due to not realizing that they are at high risk of contracting HIV, ended up contributing to the late diagnosis of HIV associated with heterosexual transmission (24) .…”
Section: Discussionmentioning
confidence: 99%
“…forefront and signal women's need to disengage themselves from the idea of a sexual life with multiple partners. The possibility of personalizing HIV is intrinsically linked with ways of moralizing sexuality, or even with ignorance, where accusatory nature is still attributed to living in these conditions (4) . Thus, it opposes the study on the media that pointed to the mobilization of specific speeches, metaphors and visual resources, as promoters of a better understanding on how HIV can be acquired and prevented.…”
Section: Descriptoresmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards experiences of prejudice/discrimination, this study also showed that the family is responsible for a large portion of them, in the form of separating household utensils, rooms, and food. Such false beliefs about HIV infection coexist socially with medical knowledge, which is widely disseminated through media campaigns (Hamann, Pizzinato, Weber, & Rocha, 2017;Moreira, França, Jacob, Cabral, & Martirani, 2018). The presence of such mode of representation, founded from an anthropological (Laplantine, 1986) and cognitive prototypical (Bishop, 2000) perspective, has already been analyzed in detail (Apostolidis & Dany, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, partindo do ponto de que as relações sexuais estão além da prática tradicional, os serviços especializados devem priorizar a desconstrução de estereótipos e problematização das noções de exposição, vulnerabilidade e sentimento de culpa a partir de um foco amplo sobre os usuários que buscam pelo serviço. Assim, permitir que possam elaborar de forma autônoma e responsável pela sua sexualidade, bem como delinear estratégias de autocuidado em seu itinerário nas relações sexuais (24) .…”
Section: Discussionunclassified